DLiP-PPI library: An integrated chemical database of small-to-medium-sized molecules targeting protein–protein interactions - Ikeda, Kazuyoshi; Maezawa, Yuta; Yonezawa, Tomoki; Shimizu, Yugo; Tashiro, Toshiyuki; Kanai, Satoru; Sugaya, Nobuyoshi; Masuda, Yoshiaki; Inoue, Naoko; Niimi, Tatsuya; Masuya, Keiichi; Mizuguchi, Kenji; et al. (Frontiers in Chemistry, 2023)
Protein–protein interactions (PPIs) are recognized as important targets in drug discovery. The characteristics of molecules that inhibit PPIs differ from those of small-molecule compounds. We developed a novel chemical library database system (DLiP) to design PPI inhibitors. A total of 32,647 PPI-related compounds are registered in the DLiP. It contains 15,214 newly synthesized compounds, with molecular weight ranging from 450 to 650, and 17,433 active and inactive compounds registered by extracting and integrating known compound data related to 105 PPI targets from public databases and published literature. Our analysis revealed that the compounds in this database contain unique chemical structures and have physicochemical properties suitable for binding to the protein–protein interface. In addition, advanced functions have been integrated with the web interface, which allows users to search for potential PPI inhibitor compounds based on types of protein–protein interfaces, filter results by drug-likeness indicators important for PPI targeting such as rule-of-4, and display known active and inactive compounds for each PPI target. The DLiP aids the search for new candidate molecules for PPI drug discovery and is available online (https://skb-insilico.com/dlip).